Pengaruh Motivasi, Kemampuan dan Lingkungan Organisasi terhadap Kinerja Karyawan (Studi pada PT. XYZ, Perusahaan Perkebunan Swasta Nasional di Pekanbaru, Riau) - Harlen, H. (Universitas Brawijaya, Indonesia, 2009)
This research aim is to analyze and research motivation, ability, and environmental work to performance PT. XYZ Pekanbaru. The research method use is verificative and causality, and the population in this research is labour of national private plantation company (PT. XYZ Pekanbaru), based on staffing is 84 people. The technique of taken sample is Proportional Stratified Random Sampling, and the technique of data gathering use in this research is field and literature study, that consist of observation, interview and questionnaire. To determine the effect and relation of independent variable to dependent variable, is used multiple linier regression, and to test the hypothesis use statistical test. The results show that with statistical testing, the coefficient determination (Rsquare) is 71,18%, this mean that about 71,18% motivation, ability, and organizational environment have significant effect or by together significant to the labour performance of national private plantation company (PT.XYZ Pekanbaru). The result of partial testing show that organizational environment have dominant effect to the labour performance of national private plantation company (PT.XYZ). Based on the result, to increase the labour performance at national private plantation company (PT.XYZ Pekanbaru), management need to focus their attention to the organizational environment, and also motivation factor, ultimately in financial and non financial factors.